2020
DOI: 10.13057/biodiv/d210716
|View full text |Cite
|
Sign up to set email alerts
|

Variation in morphological traits of a selection of Indonesian winged bean accessions (Psophocarpus tetragonolobus) and its analysis to assess genetic diversity among accessions

Abstract: Abstract. Yulianah I, Waluyo B, Ashari S, Kuswanto. 2020. Variation in morphological traits of a selection of Indonesian winged bean accessions (Psophocarpus tetragonolobus) and its analysis to assess genetic diversity among accessions. Biodiversitas 21: 2991-3000. In Indonesia, winged bean (Psophocarpus tetragonolobus (L.) DC.) is a traditional vegetable crop grown mainly for its edible green pods. Plant breeding programs aim to produce cultivars with high production and good nutritional qualities. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Otherwise the genotypes that had green calyces commonly had green stem, blue corolla-base color, and green pod with green wings as shown by H1P-19(3), H2, and local genotypes (P2, KH1, KH3). This evidence was also shown in the previous studies conducted by Thompson and Haryono (1980), and Yulianah et al (2020). Erskine and Khan (1977) reported linkage between stem and calyx color, and also between pod and wing color.…”
Section: Qualitative Traitssupporting
confidence: 87%
See 2 more Smart Citations
“…Otherwise the genotypes that had green calyces commonly had green stem, blue corolla-base color, and green pod with green wings as shown by H1P-19(3), H2, and local genotypes (P2, KH1, KH3). This evidence was also shown in the previous studies conducted by Thompson and Haryono (1980), and Yulianah et al (2020). Erskine and Khan (1977) reported linkage between stem and calyx color, and also between pod and wing color.…”
Section: Qualitative Traitssupporting
confidence: 87%
“…In previous studies, evaluation on some winged bean accessions showed that the pod length varied from 13.70 cm -38.40 cm with the pod width between 0.82 cm and 2.90 cm. Based on the pod length, winged bean genotypes in this study belong to pod classification as being moderate pods in size except for accessions KH2 and KH3 (Yulianah et al 2020;Sari et al 2018;Sukma et al 2017). Yulianah et al (2020) also reported that the pod length could affect pod weight (g per-pod), where the genotype with shorter pods produced lower pod weight, otherwise the genotype with the longest pod produced the highest pod weight.…”
Section: Quantitative Traitsmentioning
confidence: 75%
See 1 more Smart Citation
“…Sastrapradja and Aminah Lubis (1975) reported significant phenotypic variation for both qualitative and quantitative characters amongst Javanese cultivars; for example, a remarkable range in length of pods from 12 cm to 70 cm. In recent studies, Yulianah et al (2020) have observed more modest differences between cultivar means from 13.7 to 38.4 cm, but noted that for vegetable production, pod length is a pivotal character and highly heritable (Erskine and Kesavan (1982). Also important for efficient vegetable production are the maturity characteristics of cultivars.…”
Section: Figurementioning
confidence: 99%
“…Heyne (1927) compiled the limited information available at that time for winged bean cultivation in the archipelago, but it wasn't until the mid-1970s with the work of colleagues (1975, 1978) in Bogor and of Thompson and Haryono (1980) in Jogjakarta that a comprehensive picture emerged of its cultivation in Java. More recently, Handayani et al (2015), Kuswanto et al (2016) and Yulianah et al (2020) have expanded this picture with a genetic analysis of a wider range of cultivars from Indonesia, particularly East Java.…”
Section: Introductionmentioning
confidence: 99%